2007
DOI: 10.1074/jbc.m607483200
|View full text |Cite
|
Sign up to set email alerts
|

Aβ Oligomers Induce Neuronal Oxidative Stress through an N-Methyl-D-aspartate Receptor-dependent Mechanism That Is Blocked by the Alzheimer Drug Memantine

Abstract: Oxidative stress is a major aspect of Alzheimer disease (AD) pathology. We have investigated the relationship between oxidative stress and neuronal binding of A␤ oligomers (also known as ADDLs). ADDLs are known to accumulate in brain tissue of AD patients and are considered centrally related to pathogenesis. Using hippocampal neuronal cultures, we found that ADDLs stimulated excessive formation of reactive oxygen species (ROS) through a mechanism requiring N-methyl-D-aspartate receptor (NMDA-R) activation. ADD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
699
3
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 790 publications
(756 citation statements)
references
References 61 publications
37
699
3
3
Order By: Relevance
“…Researchers have investigated the relationship between oxidative stress and neuronal binding of Aβ, which is known to accumulate in the brain tissue of AD patients. Using hippocampal neuronal cultures,investigator found that Aβ stimulated excessive formation of ROS through a mechanism requiring NMDAR activation [85] . Therefore, the dysregulation of NMDAR activity and oxidative stress may have dual deleterious roles in AD.…”
Section: Excitotoxicity In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Researchers have investigated the relationship between oxidative stress and neuronal binding of Aβ, which is known to accumulate in the brain tissue of AD patients. Using hippocampal neuronal cultures,investigator found that Aβ stimulated excessive formation of ROS through a mechanism requiring NMDAR activation [85] . Therefore, the dysregulation of NMDAR activity and oxidative stress may have dual deleterious roles in AD.…”
Section: Excitotoxicity In Neurodegenerative Diseasesmentioning
confidence: 99%
“…However, many publications over the last decade rather blamed oligomers. They were indeed shown to be responsible for the formation of tau protein tangles [11], neuronal oxidative stress [12], prolonged long-term depression [13] and inhibition of long-term potentiation [14]. Other groups linked oligomers to abnormal dendritic spine morphology, spine loss, change in synaptic receptor composition [15] and finally cell death.…”
Section: Introductionmentioning
confidence: 99%
“…However, a greater understanding of the underlying process of amyloid toxicity is pressing in order to develop medication that specifically interferes with the Ab-induced disease cascade. A number of authors reporting in vitro studies have suggested that the pathological effect of Ab oligomers is mediated by the NMDA receptor (Shankar et al, 2007;Kelly and Ferreira, 2006;De Felice et al, 2007), and that over activation of the NMDA receptor should be considered as a common principle for some major neurological diseases, including AD (Lipton and Rosenberg, 1994; Harkany et al, 2000; Mattson, 2004). Stimulation of the NMDA receptor leads to excessive entry of calcium into the cell, which activates proteases that are involved in cell death signaling.…”
Section: Discussionmentioning
confidence: 99%